Frontispiece: π‐Conjugated Macrocycles Bearing Angle‐Strained Alkynes. Issue 12 (28th February 2020) - Miki, Koji; Ohe, Kouichi
Abstract : Angle‐strained alkyne‐containing π‐conjugated macrocycles are attractive compounds both in functional materials chemistry and biochemistry. K. Miki and K. Ohe examine the recent advances in angle‐strained alkyne‐containing π‐conjugated macrocycles, highlighting their synthetic methods, the bond angles of alkynes, and their functions in their review on page 2529 ff.